THE STUDI KOMPARASI NILAI PENDIDIKAN AKHLAK DALAM BUKU TAHDZIB AL AKHLAQ KARYA IBNU MISKAWAIH DAN AYYUHA AL WALAD KARYA AL GHAZALI - Siska Itaniyah; Subhan Subhan; Endad Musaddad (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
This research aims to determine the concept of character education, character education materials and character education methods in the books Tahdzîb al Akhlâq by Ibnu Miskawaih and Ayyuhal Walad by Imam Al Ghazâlî. This research uses descriptive analysis methods or text analysis and the data collection technique used in this research is the literature study technique (library), and the data sources used in this research are the books Tahdzîb al Akhlâq by Ibnu Miskawaih and Ayyuhal Walad by Imam Al Ghazâlî. The results of this research show that there are similarities in the character education values ??emphasized by Ibnu Miskawaih and Al Ghazâlî, such as patience, honesty, generosity and compassion. These two books also emphasize the importance of having a sense of responsibility and social awareness in everyday life. However, there are differences in the approaches and methods used by these two figures in teaching character education. Ibn Miskawaih tends to use a philosophical approach and encourages deep self-reflection, while Al Ghazâlî prioritizes a practical approach and provides clear instructions regarding concrete actions that must be taken in developing good morals. Based on the results of this research, it can be concluded that character education is an important aspect in the lives of individuals and society. Through understanding and teaching the character education values ??found in these books, it is hoped that it can help in forming individuals with good morals and a better society.